Measurement and Interpretation of the Oxygen Isotope Composition of Carbon Dioxide Respired by Leaves in the Dark - Cernusak, Lucas A. (American Society of Plant Biologists, 2004)
We measured the oxygen isotope composition (δ(18)O) of CO(2) respired by Ricinus communis leaves in the dark. Experiments were conducted at low CO(2) partial pressure and at normal atmospheric CO(2) partial pressure. Across both experiments, the δ(18)O of dark-respired CO(2) (δ(R)) ranged from 44‰ to 324‰ (Vienna Standard Mean Ocean Water scale). This seemingly implausible range of values reflects the large flux of CO(2) that diffuses into leaves, equilibrates with leaf water via the catalytic activity of carbonic anhydrase, then diffuses out of the leaf, leaving the net CO(2) efflux rate unaltered. The impact of this process on δ(R) is modulated by the δ(18)O difference between CO(2) inside the leaf and in the air, and by variation in the CO(2) partial pressure inside the leaf relative to that in the air. We developed theoretical equations to calculate δ(18)O of CO(2) in leaf chloroplasts (δ(c)), the assumed location of carbonic anhydrase activity, during dark respiration. Their application led to sensible estimates of δ(c), suggesting that the theory adequately accounted for the labeling of CO(2) by leaf water in excess of that expected from the net CO(2) efflux. The δ(c) values were strongly correlated with δ(18)O of water at the evaporative sites within leaves. We estimated that approximately 80% of CO(2) in chloroplasts had completely exchanged oxygen atoms with chloroplast water during dark respiration, whereas approximately 100% had exchanged during photosynthesis. Incorporation of the δ(18)O of leaf dark respiration into ecosystem and global scale models of C(18)OO dynamics could affect model outputs and their interpretation.